Hubungan Kepercayaan Diri Mahasiswa Psikologi Islam dengan Penyelesaian Skripsi di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Erny Fitroh Nabila Muwafiqi (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2022)
The process of preparing thesis and thesis proposals certainly drains a lot of energy, time, and money, even not infrequently which is also emotionally draining so that students feel anxious and allow a feeling of laziness, anxiety to arise which leads to confusion in looking for other references and it is likely that in the eighth semester it is still at the stage of writing a thesis proposal. To be able to get through this anxiety, high self-confidence is needed in order to encourage individuals to always be enthusiastic in doing the final thesis project. The formulation of the problem in this study is Is there a relationship between the self-confidence of Islamic Psychology students and the completion of a thesis at the Kiai Haji Achmad Siddiq Jember State Islamic University? This research method uses quantitative methods with a correlational approach. The research sample was 63 students so that the entire population was sampled because the sample was below 100 or called a sampling technique using a census. Data collection techniques using observation and questionnaires/ questionnaires which contain a confidence scale and a thesis completion scale. The data analysis technique used in this study used Pearson's product moment correlation. The results of this study show a positive relationship between self-confidence and the completion of a thesis with a significance value of 0.000 and a correlation value of 0.743 which means that the higher the self-confidence of Islamic Psychology students, the higher the completion of the thesis. Then is accepted and is rejected. The process of preparing thesis and thesis proposals certainly drains a lot of energy, time, and money, even not infrequently which is also emotionally draining so that students feel anxious and allow a feeling of laziness, anxiety to arise which leads to confusion in looking for other references and it is likely that in the eighth semester it is still at the stage of writing a thesis proposal. To be able to get through this anxiety, high self-confidence is needed in order to encourage individuals to always be enthusiastic in doing the final thesis project. The formulation of the problem in this study is Is there a relationship between the self-confidence of Islamic Psychology students and the completion of a thesis at the Kiai Haji Achmad Siddiq Jember State Islamic University? This research method uses quantitative methods with a correlational approach. The research sample was 63 students so that the entire population was sampled because the sample was below 100 or called a sampling technique using a census. Data collection techniques using observation and questionnaires/ questionnaires which contain a confidence scale and a thesis completion scale. The data analysis technique used in this study used Pearson's product moment correlation. The results of this study show a positive relationship between self-confidence and the completion of a thesis with a significance value of 0.000 and a correlation value of 0.743 which means that the higher the self-confidence of Islamic Psychology students, the higher the completion of the thesis. Then is accepted and is rejected.